The conflicts between the secular and the religious in Tahmima Anam’s The Good Muslim - Amrah Abdul Majid; Dinnur Qayyimah Ahmad Jalaluddin (Penerbit Universiti Kebangsaan Malaysia, 2018)
This paper discusses the relationship between the ideologies of the secular and the religious in the process of nation-building as presented in Tahmima Anam’s The Good Muslim (2011). It centres around the conflicts between the Haque siblings, Maya and Sohail as they navigate their ways in life after the Bangladeshi Liberation War of 1971. The novel portrays how Sohail’s submission to extreme dogmatism which has led him to neglecting his son, Zaid, and Maya’s inability to tolerate her brother’s transformation, result in their estranged relationship, eventually leading to a devastating family tragedy. Using Talal Asad’s (2003) definition of the secular as an ideology that brings together different concepts and practices, and which is neither a break from religion nor a continuity of it, this paper suggests that the skirmish between the siblings is a metaphorical representation of a conflict between the secular and the religious in the efforts towards nation-building. This formulation foregrounds the importance of establishing an intricate balance between the secular and the religious, which also has the social implication of destabilizing the binary that is often drawn to differentiate between a ‘good’ and a ‘bad’ Muslim.